A new Dasysiphonia (Delesseriaceae, Rhodophyta) species discovered in the North Adriatic Sea (Mediterranean) - MA Wolf; K Sciuto; A Buosi; M Orlando Bonaca; A Fortič; A Sfriso (Gruppo di Algologia (SBI), 2023)
Dasysiphonia I.K. Lee & J.A. West is a genus of the family Delesseriaceae (Rhodophyta) including 9 taxonomically accepted species (Guiry and Guiry, 2023). Among these, only one is currently reported in the Adriatic Sea (Mediterranean): Dasysiphonia japonica (Yendo) H.-S. Kim. This invasive red seaweed is native to the Hokkaido Island (Guiry and Guiry, 2023), one of the major oyster production areas in Japan (about 700 tons a year; Hasegawa et al., 2015). The species was first recorded in Europe near an oyster culture area in Brittany (France) in 1984 and in Galicia (Spain) in 1988 (Sjøtun et al., 2008). The introduction into Europe and its dispersal in the Mediterranean is most likely due to its association with the Pacific oyster Magallana gigas (Thunberg, 1793) (Sjøtun et al., 2008). This seaweed is spreading aggressively in coastal waters with blooms that have been associated with fish die-offs (Fofonoff et al., 2018). In this study we reported the first finding of another species belonging to the genus Dasysiphonia in the Mediterranean Sea. Samplings of this taxon were carried out by the Marine Biology Station Piran of the National Institute of Biology in Slovenian coastal waters, and thalli of the putative new species were analyzed both by molecular and morphological methods and compared with the other known taxa. Samples of the invasive D. japonica were collected in different sites of the Venice Lagoon (Italy) during monitoring campaigns of the project MoVEco to assess the ecological status of the lagoon in the framework of the European Water Directive (2000/60/EC). In the phylogenetic reconstruction, based on the plastid rbcL gene, the Slovenian samples were well distinct from all the species included in the genus Dasysiphonia as well as from those which were recently transferred from the sister genus Dasya (Cassidy et al., 2022). The morphological characters were analyzed and compared with those of the species D. japonica in order to estimate the invasive potential of this new taxon.